The Meaning of the Nosi Verb "Binds" in Bima Language: A Study of Natural Semantic Metalanguage - Adawiyah, Rabiyatul (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
To bind is one of the Bima language verbs. Verbs are one of the main classes of words that are central and complex. This is proven by the constant presence of verbs in speech, which determine the presence of arguments and have the authority to determine the semantic roles in each accompanying argument. The aim of this research is to determine the mapping and explication of the verb with the meaning 'to bind'. This research uses a qualitative descriptive method, which is based on post-positivist principles and is designed to investigate scientific conditions and phenomena. The data sources are in the form of oral data, written data collected from Bima language storybooks, and language intuition. The data collection techniques used are interviews and literature study. Meanwhile, the data analysis method used is the agih method which is used in analyzing semantic structures with the theory of Natural Semantic Metalanguage in the application of changing forms and insertion or paraphrasing techniques to express the original meaning with 65 items known as explication. The verb 'binding' is mapped based on: entity, process, tool, and result. The Bima language verb with the meaning 'to bind' is expressed in the lexicon: diki, leto, sarente, wura, nggambe, wole, buhu, oka, tongge.